USE OF INNOVATIVE TECHNOLOGIES IN TEACHING PHYSICS - Fayzieva Kholida Asadovna; Muhammadova Dilafruz Akhmatovna (American Journals Publishing, 2023)
This article aims to achieve effective results in a short time without spending too much mental and physical effort in the organization of modern education, different from traditional education. In this case, in the process of teaching physics, only the necessary information is selected and the volume of information is quantitatively measured in accordance with the student's learning abilities. For this, using innovative technologies, improving the quality of physics lessons in general education schools, making students interested in lessons, creative research and independent work, and forming the skills of working in mutual cooperation are mentioned.
Keywords: non-traditional lesson, innovative technology, media, interactive, leader, exhibition tools.